2011
DOI: 10.4238/vol10-3gmr1204
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum sex steroid levels and bone mineral density with CYP17 and CYP19 gene polymorphisms in postmenopausal women in Turkey

Abstract: ABSTRACT. Many clinical conditions, including osteoporosis, are associated with serum levels of sex steroids. Enzymes that regulate ratelimiting steps of steroidogenic pathways, such as CYP17 and CYP19, are also regarded as significant factors that may cause the development of these conditions. We investigated the association of two common polymorphisms, in the promoter region (T→C substitution) of CYP17 and exon 3 (G→A) of CYP19, with bone mineral density (BMD) in the lumbar spine and femoral neck and serum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Available studies indicate that genetic variations of the CYP19A1 gene, including rs749292, are associated with hormone levels in postmenopausal women with breast cancer. 15,16 At the same time, while no data is available (according to our knowledge and literature review) on the allele and genotype frequencies for CYP19A1 rs749292 in postmenopausal women with osteopenia/osteoporosis compared to controls, results similar to ours were obtained by Yilmaz et al 17 The authors of that study investigated the frequencies of the CYP19A1 rs700518 polymorphism in patients with osteoporosis and a control group from the Turkish population. They did not observe a relationship between the studied polymorphism and the occurrence of osteoporosis, though they did report a higher occurrence of the AG genotype (63%) among the control group.…”
Section: Discussionsupporting
confidence: 69%
“…Available studies indicate that genetic variations of the CYP19A1 gene, including rs749292, are associated with hormone levels in postmenopausal women with breast cancer. 15,16 At the same time, while no data is available (according to our knowledge and literature review) on the allele and genotype frequencies for CYP19A1 rs749292 in postmenopausal women with osteopenia/osteoporosis compared to controls, results similar to ours were obtained by Yilmaz et al 17 The authors of that study investigated the frequencies of the CYP19A1 rs700518 polymorphism in patients with osteoporosis and a control group from the Turkish population. They did not observe a relationship between the studied polymorphism and the occurrence of osteoporosis, though they did report a higher occurrence of the AG genotype (63%) among the control group.…”
Section: Discussionsupporting
confidence: 69%
“…There is evidence linking CYP17 polymorphisms and estrogen synthesis variability which in turn may increase the risk for cancer [6,7,25], osteoporosis [26], Alzheimer disease [27], and also cardiovascular disease through the atherogenic process [28][29][30]; our data adds to the prior, however linking for the first time the studied CYP polymorphism with the intensity of mood symptoms in postmenopausal women. Clearly, all these conditions are steroid hormone and age-related in which genetic background may have a pivotal role over disease development and outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, Tofteng et al (2004) found that the lumbar spine (L2-L4) cross-sectional area (cm 2 ) was reduced in homozygous mutant women in Denmark, but they did not observe a significant difference in the femoral neck, and bone mineral content, BMD, and bone mineral apparent density did not differ by CYP17 genotype. However, Yilmaz et al (2011) found that the CYP17 gene polymorphism was associated with osteoporosis in post-menopausal women in Turkey, and Yamada et al (2005) suggested that CYP17 contains susceptibility loci for increased BMD in post-menopausal and pre-menopausal *OR = odds ratio adjusted, homozygous wild vs heterozygous and homozygous mutant. CI = confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…There are several sites of potential occurrence for osteoporotic fracture including the spine, hip, distal forearm, and proximal humerus (El-Heis et al, 2013). The major determinant of bone strength and osteoporotic fracture risk is BMD (Gennari et al, 2005); BMD decrease can be accelerated by factors such as menopause and insufficient dietary calcium (Yilmaz et al, 2011). Osteoporosis is a polygenic disorder resulting from the interaction of common polymorphic alleles and environmental factors (Somner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation